2019
DOI: 10.1038/s41591-019-0593-1
|View full text |Cite|
|
Sign up to set email alerts
|

Pulmonary venous circulating tumor cell dissemination before tumor resection and disease relapse

Abstract: Data Availability Statement The majority of data generated or analysed during this study are included in this published article. The sequencing data are available through the Cancer Research UK & University College London Cancer Trials Centre for non-commercial research purposes and access will be granted upon review of a project proposal that will be evaluated by a TRACERx data access committee and entering into an appropriate data access agreement subject to any applicable ethical approvals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 33 publications
6
138
0
Order By: Relevance
“…19,35 These alterations in osteoblastic gene regulators, including ALPL, RUNX2, SPP1, CDH11, and TNFSF11, were present in CTCs and not in paired cfDNA. 46,47 Our collective data suggest that CTCs harbor critical genomic information that may be missed by cfDNA analysis alone. Furthermore, Cohen's kappa analysis of CTCs and cfDNA showed that AR has a discordance in the opposite direction, with greater detection in cfDNA than CTC DNA.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…19,35 These alterations in osteoblastic gene regulators, including ALPL, RUNX2, SPP1, CDH11, and TNFSF11, were present in CTCs and not in paired cfDNA. 46,47 Our collective data suggest that CTCs harbor critical genomic information that may be missed by cfDNA analysis alone. Furthermore, Cohen's kappa analysis of CTCs and cfDNA showed that AR has a discordance in the opposite direction, with greater detection in cfDNA than CTC DNA.…”
Section: Discussionmentioning
confidence: 82%
“…Additional larger studies of paired samples prospectively collected in clinically annotated datasets of patients with cancer in different disease states and during different treatments are needed to define whether CTCs, cfDNA, or a combined approach has greater clinical utility. 46,47 Our collective data suggest that CTCs harbor critical genomic information that may be missed by cfDNA analysis alone. Yet, reliance on CTC genomic data alone has limitations because many patients with metastatic prostate cancer lack detectable CTCs, particularly in earlier disease settings, limiting the clinical utility of this approach.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, Chemi et al evaluated the prognostic role of CellSearch-detected pulmonary venous (PV) CTCs, at the time of surgery, in 100 early-stage NSCLC patients, enrolled into the Tracking Non-Small Cell Lung Cancer Evolution through Therapy (TRACERx) trial. Although further studies are needed to confirm the clinical utility of PV-CTCs, the authors demonstrated that patients with detectable CTCs are more likely to experience disease recurrence [15].…”
Section: Circulating Tumor Cellsmentioning
confidence: 98%
“…Another proof-of-concept example is the large number of studies reporting the potential clinical utility of androgen receptor splice variant 7 (AR-V7) detection in CTCs as a marker for treatment selection in patients with castration-resistant prostate cancer (CRPC) [110][111][112][113][114][115][116][117][118][119]. Along these lines, in a recent case report within the TRACERx study in non-small cell lung cancer (NSCLC), exome sequencing of pulmonary venous CTCs (PV-CTC) collected at surgery showed that CTCs at surgery are more similar to subsequent metastatic disease than to the primary tumor, highlighting the potential of PV-CTCs as early predictors of NSCLC recurrence after surgery [120].…”
Section: Clinical Value Of Ctcsmentioning
confidence: 99%